Nutritional interventions for heart failure patients who are malnourished or at risk of malnutrition or cachexia: a systematic review and meta-analysis - Habaybeh, Dina; de Moraes, Mariana Bordinhon [UNESP]; Slee, Adrian; Avgerinou, Christina (Springer Nature, 2020)
Malnutrition is common in heart failure (HF), and it is associated with higher hospital readmission and mortality rates. This review aims to answer the question whether nutritional interventions aiming to increase protein and energy intake are effective at improving outcomes for patients with HF who are malnourished or at risk of malnutrition or cachexia. Systematic searches of four databases (Medline, Embase, CINAHL and Cochrane Central Register of Controlled Trials (CENTRAL)) were conducted on 21 June 2019. Randomized controlled trials (RCTs) or other interventional studies using protein or energy supplementation for adult HF patients who are malnourished or at risk of malnutrition or cachexia were included. Two independent reviewers assessed study eligibility and risk of bias. Five studies (four RCTs and one pilot RCT) met the inclusion criteria. The majority of studies were small and of limited quality. The pooled weighted mean difference (WMD) for body weight showed a benefit from the nutritional intervention by 3.83 kg (95% confidence interval (CI) 0.17 to 7.50, P = 0.04) from three trials with no significant benefit for triceps skinfold thickness (WMD = − 2.14 mm, 95% CI − 9.07 to 4.79, P = 0.55) from two trials. The combination of personalized nutrition intervention with conventional treatment led to a decrease in all-cause mortality and hospital readmission in one study. Findings of this review suggest that nutritional interventions could potentially improve outcomes in HF patients who are malnourished or at risk of malnutrition. However, the strength of the evidence is poor, and more robust studies with a larger number of participants are needed.
Keywords: Heart failure; Malnutrition; Nutritional interventions; Oral nutritional supplements